Station to Station : a catalogue of 31 photographs by Canadian artists mounted on billboards in stations of the Toronto Transit Commission's subway system from September 5 to November 30, 1979. (Toronto : A Space, 1979)
Applebaum, Isaac ; Besold, Bobbe ; Collins, Paul ; Cooper, Jeremy ; Fromer, Lorne ; Gallagher, Chris ; General Idea ; Grainger, Irene ; Greenwood, Gary ; Grenier, Serge ; Hinton, John Henry ; Hlynsky, David ; Holownia, Thaddeus ; Holzberg, Ben Mark ; Ives, Suzanne ; etc.
Station to Station : a catalogue of 31 photographs by Canadian artists mounted on billboards in stations of the Toronto Transit Commission's subway system from September 5 to November 30, 1979. An A Space Satellite project.
Engels
kunstcatalogus
Keywords: Canada